The development of Danube Ports amid war and post-war recovery of the Ukraine - Horoshkovа, L. A.; Horoshkov, S. V.; Korniichuk, Y. D. (Man and Environment. Issues of Neoecology, 2024)
Purpose: assessment of the development of Danube Ports amid war and post-war recovery of the Ukraine as part of the security system for Ukraine, Europe, and the world as a whole.Меthods. In the research general scientific (analysis and synthesis, induction and deduction, analytical grouping) and special (abstraction, modelling, etc.) methods of studying economic phenomena and processes have been used. The object of the study is the Danube river ports.Results. The conducted analysis showed that in the conditions of war and the blockade of the ports of Greater Odessa, export transportation through the Ukrainian Danube ports of Reni, Izmail, and Ust-Danube has been activated. This was also facilitated by the dredging works in the Bystre estuary, which allowed its transport capabilities to be used for the passage of vessels with a draft of up to 6.5 meters, and not only the Romanian Sulina canal. The analysis showed that, in addition to positive results for Ukrainian ports, there was also an increase in cargo handling volumes in Romanian ports, for example, the Sulina port has shown an increase in cargo movement volumes in recent years. Overall, if we compare the growth rates in the direction of Danube-Black Sea and in the opposite direction, the preference is given to the Danube-sea direction. Regarding transportation through the Danube-Black Sea canal, recent years have also seen an increase in cargo transportation volumes, but this is mainly due to international transportation. Domestic transportation does not show similar dynamics. The Constanta port has also been increasing cargo handling volumes in recent years due to sea transportation, but river transportation is also growing, although not as significantly. Unlike the mentioned ports, the Romanian port of Galati has been decreasing cargo handling volumes since 2021. The reason for this is that, among the two routes considered - the Danube and the Danube-Black Sea to the Constanta port, preference is given to the latter. Conclusions. The conducted research has shown that the further expansion of navigation along the Danube using the routes Ukraine - Galati, Ukraine - Regensburg, and Ukraine-Constanta (via the Danube) will ensure the effectiveness of the mentioned ports and create additional conditions for the development of transport logistics in the Danube region as part of the security system for Ukraine, Europe, and the world as a whole.An additional advantage of such decisions is their environmental orientation, since among all types of transport, water transport is the most environmentally friendly.